2012
DOI: 10.1029/2011gl050324
|View full text |Cite
|
Sign up to set email alerts
|

Total and monomethyl mercury in fog water from the central California coast

Abstract: Total mercury (HgT) and monomethyl mercury (MMHg) concentrations in fog collected from 4 locations in and around Monterey Bay, California during June‐August of 2011 were 10.7 ± 6.8 and 3.4 ± 3.8 ng L−1respectively. In contrast, mean HgT and MMHg concentrations in rain water from March‐June, 2011 were 1.8 ± 0.9 and 0.1 ± 0.04 ng L−1 respectively. Using estimates of fog water deposition from 6 sites in the region using a standard fog water collector (SFC), depositions of HgT and MMHg via fog were found to range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 28 publications
3
44
0
Order By: Relevance
“…In the original work to quantify Hg in marine fog, the CASCC was set to turn on/off at fixed times of day (22:00-09:00 local time), since fog was regularly occurring at night and almost never of sufficient density to collect a sample during the day (Weiss-Penzias et al, 2012). However, this meant that the sampler could have been on for many hours before the onset of fog and thus may have accumulated gases and particles.…”
Section: Fog Water Collector Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the original work to quantify Hg in marine fog, the CASCC was set to turn on/off at fixed times of day (22:00-09:00 local time), since fog was regularly occurring at night and almost never of sufficient density to collect a sample during the day (Weiss-Penzias et al, 2012). However, this meant that the sampler could have been on for many hours before the onset of fog and thus may have accumulated gases and particles.…”
Section: Fog Water Collector Detailsmentioning
confidence: 99%
“…However, in this study, low MMHg concentrations overall were found (0.14 ± 0.10 ng L -1 ), with no seasonal variability that would have been indicative of seasonal DMHg evasion from ocean due to coastal upwelling. Subsequently, summertime marine fog water MMHg concentrations from samples collected in Santa Cruz, California were found to be enhanced (3.4 ± 3.8 ng L -1 , n = 8) relative to rain, with an apparent biotic source of MMHg associated with coastal upwelling (Weiss-Penzias et al, 2012). Similarly, MMHg of marine origin was found to accumulate in lichen on the coast of the Arctic Ocean (St. Pierre et al, 2015) and may represent a health risk to native populations who eat the caribou that feed off of the lichen.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Weiss-Penzias et al [99] have investigated total mercury (HgT) and monomethyl mercury (MMHg) concentrations in fog water. They reported mean HgT concentrations of 10.7 ± 6.8 ng/L and mean MMHg concentrations of 3.4 ± 3.8 ng/L.…”
Section: Impacts On Air Qualitymentioning
confidence: 99%
“…Recent research even shows the presence of methylmercury-a toxic bioaccumulatorin "pristine" coastal fog, which apparently originates naturally from marine aerosol [ Weiss-Penzias et al , 2012 ].…”
Section: A Global Perspective On Fog-forming Aerosolsmentioning
confidence: 99%